2021
DOI: 10.1002/jcla.23802
|View full text |Cite
|
Sign up to set email alerts
|

Association of alpha‐thalassemia and Glucose‐6‐Phosphate Dehydrogenase deficiency with transcranial Doppler ultrasonography in Nigerian children with sickle cell anemia

Abstract: Background Stroke is a devastating complication of sickle cell anemia (SCA) and can be predicted through abnormally high cerebral blood flow velocity using transcranial Doppler Ultrasonography (TCD). The evidence on the role of alpha‐thalassemia and glucose‐6‐phosphate dehydrogenase (G6PD) deficiency in the development of stroke in children with SCA is conflicting. Thus, this study investigated the association of alpha‐thalassemia and G6PD(A−) variant with abnormal TCD velocities among Nigerian children with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…Coexistent genetic factors in the study population, sample size, whether TAMMV or PSV was measured, and geographical spread of the participants might contribute to variation in the proportion of children with SCD who have conditional blood velocity in the cerebral arteries. A single-institution study in Nigeria showed that the coexistence of alpha thalassaemia trait protects against a rise in cerebral artery blood velocity, whereas no significant association with glucose-6-phosphate dehydrogenase was observed 23. That the parameter used could affect the proportion with conditional velocity is suggested by the similarity in the percentage in the TAMMV cohort in this study (10%) and that of 9.9% from another multicentre survey of children with SCD in Brazil during which TAMMV was measured 30…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coexistent genetic factors in the study population, sample size, whether TAMMV or PSV was measured, and geographical spread of the participants might contribute to variation in the proportion of children with SCD who have conditional blood velocity in the cerebral arteries. A single-institution study in Nigeria showed that the coexistence of alpha thalassaemia trait protects against a rise in cerebral artery blood velocity, whereas no significant association with glucose-6-phosphate dehydrogenase was observed 23. That the parameter used could affect the proportion with conditional velocity is suggested by the similarity in the percentage in the TAMMV cohort in this study (10%) and that of 9.9% from another multicentre survey of children with SCD in Brazil during which TAMMV was measured 30…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, the country that has the largest population of people with SCD (3 million) and the highest SCD birth rate of 150 000 per year,15–18 previous studies of the percentage who have conditional blood velocity in the cerebral arteries have been in single healthcare institutions and yielded variable results 19–24. The objective of this study is to obtain multicentre data to represent the general situation in the country and so facilitate the development of policy on the care of children with SCD who have conditional blood velocity in the cerebral arteries.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the lack of facilities/resources, we did not assay the activity of vWF nor determine the presence of some genetic influencers of SCD, such as HbF and Alpha Thalassemia, which could impact several parameters in patients with SCA including the TCD velocity. 40,41 Despite these limitations, this study was able to establish, for the first time in our locality, that children with SCA had higher levels of FVIII and vWF. Furthermore, our study established that there exists a relationship between abnormal TCD velocity, platelet count, and left middle cerebral artery.…”
Section: Discussionmentioning
confidence: 77%
“…A total of 571 publications passed this screening (eFigure 1 in Supplement 1 , eTable 1 in Supplement 2 ). 8 , 11 , 12 , 13 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ...…”
Section: Methodsunclassified